Banking, Monetary target policy and Stock market shock - Hossein Eslami Mofid Abadi; Marzieh Ebrahimi Shaghaghi; Morteza Taherifard (Mathematics and Modeling in Finance, 2022)
This research has been investigated, economy and balance-sheet effects of the money growth rate targeting. According to financial statements of the banking network and national accounts, using dynamic stochastic general equilibrium New Keynesian and statistical data for the period 1991-2019.For estimating parameters, is used New Keynesian DSGE model and Bayesian method. This paper verify the validity of the model by analyzing the impulse response functions and Brooks and Goleman test. The results of the model indicate that the effect of negative the money growth rate targeting, reduce deposits, reduce loans interest rates, lead to reducing banks' resources, bank lending and then the health of the banks would compromise. In this way, investment and production will be reduced. Also, the effect of stock prices increasing, deposit, loan decrease and investment and production increase. Therefore, this research suggests the policy of negative the money growth rate targeting coincide with the policy of raising interest rates and stock price rising.